Problematyka niepełnosprawności w polskich czasopismach naukowych - analiza wybranych przykładów = The issue of disability in Polish academic journals ? the analysisof selected cases - Mirkiewicz, Beata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article discusses selected Polish academic journals dealing with the issue of disability, and analyses their significance. The review concerns the electronic journals indexed by the ARIANTA database. The article also analyses the topic structure of the selected journals on the basis of the PEDAGOG and SPORT reference databases.
Keywords: czasopisma naukowe; czasopisma polskie; osoby z niepełnosprawnością; niepełnosprawność; scientific journals; Polish magazines; people with disabilities; disability